PENGGUNAAN METODE SOSIODRAMA UNTUK MENINGKATKAN PARTISIPASI SISWA DALAM PEMBELAJARAN SOSIOLOGI KELAS XI IPS 1 SMAN 5 PONTIANAK - Prasetyaningrum, Uniek (Universitas Tanjungpura, 2022)
This research is motivated by the inability of learning sociology in class XI IPS 1 SMAN 5 Pontianak to achieve one of the goals of learning sociology in high school, which is to direct students to understand life phenomena and train students to solve problems. This study aims to determine the extent of the socio-drama method. Can increase student participation and know also the obstacles that are often faced in learning, especially learning sociology. This research is a Classroom Action Research (CAR) carried out in three cycles, each cycle consisting of 4 stages, namely planning, implementation, observation, and reflection. The subjects of this study were students of class XI IPS 1 SMAN 5 Pontianak, totaling 36 students. The performance of the sociodrama method is carried out in the following ways, (1) the first cycle uses the teacher's explanation of the sociodrama method with social conflict material, (2) the second cycle uses group discussions to make drama scripts., and (3) cycle III uses group discussions accompanied by teacher explanations and student summaries and makes drama scripts from the results of these summaries and describes them. The results of this study indicate that the application of the socio-drama method can increase student participation in class XI IPS 1 at SMAN 5 Pontianak. The results of the first cycle were 55.55% (56%), the second cycle increased to 88.88% (89%), and the third cycle increased to 100%. The obstacle faced at the beginning of the application of the sociodrama method was that there were still students who had difficulty in determining the time allocation for staging a drama.